The structure of consumer finance industry in emerging market (Empirical evidence: Indonesia 2000-2015) - Johan, Suwinto (Jurnal Manajemen Bisnis dan Kewirausahaan, 2017)
This paper aims to study the structure of the Indonesia Finance Company Industry over the period 2001-2015. The finance company industry is growing rapidly from Rp. 37 trillion in 2001 to Rp. 425 trillion in 2015 with a compounded annual growth rate (CAGR) of 18%. At the same time, the number company in the industry has reduced from 245 in 2001 to 203 in 2015. We use the Concentration Ratio (CR) and Herfindahl-Hirschman Index (HHI) to measure the structure of the industry. Our sample consists of 97 companies in 2001 to 125 companies in 2015. The empirical results show that the Indonesian finance company industry is not highly concentrated. The HHI has reached 451 in 2015 from 313 in 2010. There has been a significant increase in the concentration ratio from 2000 to 2015, especially the concentration in CR4, CR8, and CR12. The CR4 has reached 34,12%, CR8 has reached 51,15%, CR12 61,72%, and CR20 by 76,57%. The CR4 means that the top 4 finance companies have controlled 34,12% of the total productive assets of the financing industry by 2015. The CR4 has almost reached the oligopoly category. However, there is a potential for higher concentration if we group the companies by the shareholders’ ownership, due to the controlling issue of the shareholders.